А.ДАБЫЛОВТЫҢ «БАҲАДЫР» ДӘСТАНЫНДА ФОЛЬКЛОРЛЫҚ МОТИВЛЕР - Алланазаров, Е. (ILIM hám JÁMIYET, 2021)
The article describes the use of traditional programs in folk epics when creating an epic about the folk poet A. Dabilov, coverage of new sides of the realistic life of traditional programs, as well as inspired epics of folk poets of a deeply philosophical and philosophical nature, patriotic, especially friendship of peoples, real life from a scientific point of view is interpreted in all senses as an emotionally rich work.